Thermal-hydraulic Feasibility Study of a Convex shaped Fast Reactor Core. (December 2017) - Chitose, Keiko; Mochizuki, Hiroyasu; Takaki, Naoyuki
Abstract: The objective of the present study is to evaluate the temperature profile of a convex shaped reactor core to confirm the thermal hydraulic feasibility. The convex core configuration intends to achieve negative reactivity insertion by fuel compaction in case of CDA. For the preliminary study, a convex core with fuel length 1.585m in the inner-core region and 0.52m in the outer-core region is modeled by RELAP5-3D code. The calculation model consists of the reactor core with 10 different channels, two IHXs, two main pumps, and lower and upper plena. The basic parameters are assumed similar to the existing study for Monju and JSFR. Considering well-balanced flow distribution to the core, the linear heat rate of the outer-core region is within the upper limit. The pressure loss and temperature distribution of the core are calculated. It is confirmed that no major issue to deny the feasibility of the fundamental thermal-hydraulics.